Early Mini-Invasive Treatment of Persistent Cervical Dysplasia: Clinical Outcome and Psycho-Relational Impact - Plotti, Francesco; Rossini, Gianmarco; Ficarola, Fernando; De Cicco Nardone, Carlo; Montera, Roberto; Guzzo, Federica; Luvero, Daniela; Fabris, Silvia; Angioli, Roberto; Terranova, Corrado (Frontiers in Surgery, 2022)
Introduction: After diagnosis of L-SIL, 77.3% have a persistent infection and anomalous Pap Test results. Many of these patients have highlighted psychological consequences (anxiety, fear of cancer, changes in body image, hypochondria) and sexual problems. Several studies suggested that clearance of HR-HPV infection could be accelerated by cervical excisional procedures especially in L-SIL. In consideration of the psychological implications for HPV infection and related dysplasia in patients with CIN1 at PAP-smear and HR-HPV positivity at least for 6 months we decided to plan a prospective study where we try to anticipate excisional cervical using a minimally invasive treatment: t-LEEP (Thin Loop Electrosurgical Excision Procedure). The aims of study are analyzed clearance of HR-HPV after 6 and 12 months, clinical outcome related to t-LEEP and the psycho-relational impact at 12 months after t-LEEP. Materials And Methods: We enrolled patients with diagnosis of L-SIL at PAP-smear and HR-HPV positivity with a persistent CIN 1 (at least for 6 months), confirmed by cervical biopsy. All enrolled patients underwent t-LEEP. We follow prospectively and performed for all patients HPV DNA test at 6 months (T1) and 12 months (T2), and STAI-Y and FSFI scores at T0 and T2. Results: We prospectively enrolled 158 patients, 22 are excluded for the established criteria. Patients with HR-HPV and CIN 1 lesions treated with t-LEEP had overall clearance of 83.8% at T2. In subgroups analysis at T2 we have a regression: in smoker 71.8%, in contraceptive users 69.5%, in patients aged < 25y 100%, aged 25-30y 85%, aged 30-35y 94.4%, aged 35-40y 92 % and aged ≥40y 89.1 %, in HPV-16 96.4%, in HPV-53 89.5%, in HPV-18 87.5%, in HPV-31 86.6%, in coinfected 3.5%. STAI-Y and FSFI after t-LEEP (T2) are statistically significant with a reduction of anxiety status and improve of sexual function. Conclusions: Based on these results, the use of t-LEEP in patients with persistent CIN 1 and HPV-HR at least for 6 months could be useful for accelerate HPV-HR clearance, in particular, for a subpopulation patient with an increased risk of progression and/or patients with psychological and sexual consequences of carrying a HR-HPV infections.